Reducing the gender gap in the physics classroom: How sufficient is interactive engagement? - Steven J. Pollock; Noah D. Finkelstein; Lauren E. Kost (Physical Review Special Topics. Physics Education Research, 2007)
Previous research [Lorenzo et al., Am. J. Phys. 74, 118 (2006)] demonstrated that the difference in performance between male and female students can be reduced and even eliminated, in consistent fashion, by using interactive engagement techniques in the introductory physics classroom. The present paper describes similar studies in a different, large research university and finds that the use of interactive engagement techniques does not necessarily reduce the gender gap. Furthermore, in the environments studied, there is a gap in learning gains between male and female students (p<0.01) whether partially or fully interactive classroom techniques are used. Our findings suggest that engaging students in interactive educational environments is not sufficient to reduce the gender gap, and we find instances where despite significant learning gains by all students, the gender gap is increased. There is indication that there are both student and instructor effects that impact the gender gap, which are the subjects of ongoing studies.